Study of structural imbalances in agricultural engineering - George Abuselidze; Valerii Kotliarov; Svitlana Petrychuk; Olga Danylevska-Zhugunisova; Olga Mohylevska (E3S Web of Conferences, 2022)
The authors emphasized that the development of the agricultural machinery industry is inextricably linked with the development of agricultural production, and consequently, changes in land use forms and the development of agricultural science, which, in turn, are conditioned by the current socio-political conditions and progress in the field of agricultural knowledge. It is proved that the impetus for the development of domestic agricultural machinery is the agricultural holdings. The authors focused on the fact that state support and regulation of the agricultural machinery market was proposed by stimulating the renewal of the technical park through the improvement of financial leasing, the reduction in the cost of medium- and long-term loans, and the improvement of the procedures for putting equipment into operation. It is noted that in order to preserve the process of updating the machine and tractor fleet and high-tech equipment in agriculture, it is necessary to ensure the effectiveness of state programs to support domestic agricultural enterprises, which will allow the restoration of their financial viability, and this in turn will serve as an impetus to the development of the market of agricultural machinery due to the growing demand for technical means.
Keywords: Q13; Q14; Q16; Q18; 330; Mechanical engineering; Agricultural industry; Financial and economic aspect; Industry imbalances